Cuticle degrading enzyme production by some isolates of the entomopathogenic fungus, Metarhizium anisopliae (Metsch.) (Journal of Bio-Science, 2014)
Context: Entomopathogenic fungi have been recognized as viable alternate options to chemicals in insect pest control. Unlike other potential biocontrol agents, fungi do not have to be ingested to infect their hosts but invade directly through the cuticle. Entry into the host involves both enzymic degradation of the cuticle barrier and mechanical pressure. Production of a range of cuticle degrading enzymes is an important event in the interaction of entomopathogenic fungi and host. Enzyme secretion is believed to be a key contributor for the virulence of a fungal isolate. Objectives: The potentiality of nine isolates of M. anisopliae were tested to produce to produce three important cuticle degrading enzymes, viz., chitinase, protease and lipase. Materials and Methods: Nine isolates of M. anisopliae were evaluated for chitinase, protease and lipase enzyme production by determining the enzyme index and activities. Results: Chitinase index of these isolates were ranged from 1.5 to 2.2 and chitinolytic activity from 0.525 to 1.560 U/ml. The isolates showed protease index in the range of 1.2 to 3.3 and the activity ranged from 0.020 to 0.114 U/ml. Lipase index ranged from 1.15 to 7.0 and the enzyme activity ranged from 0.153 to 0.500 U/ml. A strong relationship was observed between virulence of the isolates and cuticle degrading enzyme production as increased enzyme production was observed for virulent isolates. Conclusion: In the present study three isolates as (MIS2, MIS7 and MIS13) demonstrated cuticle degrading enzyme (CDE) that indicate higher virulence based on the bioassay conducted earlier by the authors as strongly substantiating the role of CDEs is considered the virulence of Metarhizium isolates. So, these isolates may be as ecofriendly insect-pest control agent in future. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17648 J. bio-sci. 20: 25-32, 2012